Serotype diversity and antimicrobial susceptibility profiles of Actinobacillus pleuropneumoniae isolated in Italian pig farms from 2015 to 2022 - Flavia Guarneri; Claudia Romeo; Federico Scali; Simona Zoppi; Nicoletta Formenti; Antonio Marco Maisano; Salvatore Catania; Marcelo Gottschalk; G. Loris Alborali (Veterinary Research, 2024)
Abstract Actinobacillus pleuropneumoniae (APP) is a bacterium frequently associated with porcine pleuropneumonia. The acute form of the disease is highly contagious and often fatal, resulting in significant economic losses for pig farmers. Serotype diversity and antimicrobial resistance (AMR) of APP strains circulating in north Italian farms from 2015 to 2022 were evaluated retrospectively to investigate APP epidemiology in the area. A total of 572 strains isolated from outbreaks occurring in 337 different swine farms were analysed. The majority of isolates belonged to serotypes 9/11 (39.2%) and 2 (28.1%) and serotype diversity increased during the study period, up to nine different serotypes isolated in 2022. The most common resistances were against tetracycline (53% of isolates) and ampicillin (33%), followed by enrofloxacin, florfenicol and trimethoprim/sulfamethoxazole (23% each). Multidrug resistance (MDR) was common, with a third of isolates showing resistance to more than three antimicrobial classes. Resistance to the different classes and MDR varied significantly depending on the serotype. In particular, the widespread serotype 9/11 was strongly associated with florfenicol and enrofloxacin resistance and showed the highest proportion of MDR isolates. Serotype 5, although less common, showed instead a concerning proportion of trimethoprim/sulfamethoxazole resistance. Our results highlight how the typing of circulating serotypes and the analysis of their antimicrobial susceptibility profile are crucial to effectively manage APP infection and improve antimicrobial stewardship.